Detection of schistosoma spindale ova and associated risk factors among Malaysian cattle through coprological survey - Tan, Tiong Kai; Low, Van Lun; Lee, Soo Ching; Panchadcharam, Chandrawathani; Kho, Kai Ling; Koh, Fui Xian; Sharma, Reuben Sunil Kumar; Jaafar, Tariq; Lim, Yvonne Ai Lian (Hokkaido University, 2015)
The present study was conducted to determine the occurrence of Schistosoma spindale ova and its associated risk factors in Malaysian cattle through a coprological survey. A total of 266 rectal fecal samples were collected from six farms in Peninsular Malaysia. The overall infection rate of S. spindale was 6% (16 of 266). Schistosoma spindale infection was observed in two farms, with a prevalence of 5.4% and 51.9%, respectively. This trematode was more likely to co-occur with other gastro-intestinal parasites (i.e., Dicrocoelium spp., Paramphistomum spp., strongyle, Eimeria spp. and Entamoeba spp.). Chi-square analysis revealed that female cattle are less likely to get S. spindale infection as compared to male cattle (OR ＝ 0.3; 95% CI ＝ 0.08-1.06; p ＜ 0.05), and cattle weighing lower than 200 kg, were significantly at higher risk than those higher than 200 kg (OR ＝ 5; 95% CI ＝ 1.07-24.79; p ＜ 0.05) to the infection. Multivariate analysis confirmed that among the cattle in Malaysia, the age (cattle with two year old and higher: OR ＝ 21; 95% CI ＝ 2.48-179.44; p ＜ 0.05) and weight (weighing 200 kg and lower: OR ＝ 17; 95% CI ＝ 3.38-87.19; p ＜ 0.05) were risk factors for S. spindale infection among Malaysian cattle.